Multislice computerized tomography coronary angiography can be a comparable tool to intravascular ultrasound in evaluating “true” coronary artery bifurcations - Radunović, Anja; Vidaković, Radosav; Timčić, Stefan; Odanović, Natalija; Stefanović, Milica; Lipovac, Mirko; Krupniković, Kosta; Mandić, Aleksandar; Kojić, Dejan; Tomović, Milosav; Ilić, Ivan (Frontiers in Cardiovascular Medicine, 2023)
Aims: Coronary bifurcation atherosclerosis depends on its angles, flow and extensive branching. We investigated the ability of CT coronary angiography (CTCA) to determine atherosclerotic plaque characteristics of “true” bifurcation compared to intravascular ultrasound (IVUS) and the influence on side branch (SB) fate after PCI. Methods and results: Seventy-two “true” bifurcations from 70 patients were included in the study. Most of the bifurcations were left anterior descending (LAD) – diagonal (D) [50/72 (69.4%)]. Longitudinal plaque evaluation at the polygon of confluence (carina and 5mm proximal and distal in the main branch (MB)) showed that carina side MB and SB plaque had occurred with the lowest incidence with fibro-lipid structure (115±63 HU and 89±73 HU, p<0.001 for all). Bland-Altman analysis showed discrepancy in measuring mainly lumen and vessel area between CTCA and IVUS in proximal MB (lumen 5.10, 95%CI[4.53,5.68]mm2, p<0.001; vessel -1.42, 95%CI[-2.63,-0.21]mm2, p=0.023) carina MB (lumen 3.74, 95%CI[3.37,4.10]mm2, p<0.001; vessel -0.48, 95%CI[-1.45,0.48]mm2, p=0.322) and distal MB (lumen 4.72, 95%CI[4.27,5.18]mm2, p<0.001; vessel 0.62, 95%CI[-0.53,1.77]mm2, p=0.283) (proximal 11.27% and 11.6% respectively, carina 34.87%, 4.79%, distal 30.77%, 6.05%, minimal lumen diameter (MLD) 69.59%, 28.18%). Significant correlation existed between average plaque density on CTCA with percentage of calcified plaque on IVUS tissue characterization (proximal r=0.307/p=0.024, carina 0.469/0.008, distal 0.339/0.024, MLD 0.318/0.020). Circumferential plaque in the proximal MB segment remained an independent predictor of SB compromise [OR 3.962 (95 % CI 1.170 – 13.418)]. Conclusions: Atherosclerotic plaque detection and characterization by CT coronary angiography in non-left main “true” coronary bifurcations can provide useful information about bifurcation anatomy and plaque distribution that can predict outcomes after provisional stenting, thus guiding the interventional strategy to bifurcation PCI. CTCA is an acceptable tool in complex bifurcations’ evaluation compared to IVUS with limitations regarding advanced atherosclerotic lesions and can provide important predictive information for PCI.